Cahiers des Sciences Familiales et Sexologiques. (Louvain-la-Neuve : Université de Louvain, 1990)
Fonds Suzan Daniel (FSD)
Periodiciteit
Redactie: 54, Grand Rue, B, 1348 Louvain-La-Neuve
Frans
Periodiek